2010
DOI: 10.1099/mic.0.033241-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of host cell polarity and leading edge properties in Pseudomonas type III secretion

Abstract: Type III secretion (T3S) functions in establishing infections in a large number of Gram-negative bacteria, yet little is known about how host cell properties might function in this process. We used the opportunistic pathogen Pseudomonas aeruginosa and the ability to alter host cell sensitivity to Pseudomonas T3S to explore this problem. HT-29 epithelial cells were used to study cellular changes associated with loss of T3S sensitivity, which could be induced by treatment with methyl-beta-cyclodextrin or perfrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 69 publications
0
25
1
Order By: Relevance
“…Thus, infection studies with P. aeruginosa revealed that some cell lines are resistant against T3S-mediated protein injection, indicating the requirement of certain host cell properties for efficient effector protein translocation (357,471). This observation was supported by the finding that the alteration of the host plasma membrane composition renders cells insensitive against T3S by P. aeruginosa (55). It was already previously proposed that the formation of a functional T3S translocon occurs preferentially in specific microdomains of the host cell membrane that are rich in cholesterol and glycosphingolipids (490).…”
Section: Port Of Entry For Effector Proteins-the Translocon and The Tmentioning
confidence: 91%
“…Thus, infection studies with P. aeruginosa revealed that some cell lines are resistant against T3S-mediated protein injection, indicating the requirement of certain host cell properties for efficient effector protein translocation (357,471). This observation was supported by the finding that the alteration of the host plasma membrane composition renders cells insensitive against T3S by P. aeruginosa (55). It was already previously proposed that the formation of a functional T3S translocon occurs preferentially in specific microdomains of the host cell membrane that are rich in cholesterol and glycosphingolipids (490).…”
Section: Port Of Entry For Effector Proteins-the Translocon and The Tmentioning
confidence: 91%
“…Consistent with actin playing a role in T3S translocation, studies of Yersinia, Shigella, and enterohemorrhagic Escherichia coli have implicated a role of actin in enhanced T3S effector translocation (41,42,43,64), but the underlying mechanism remains unknown. Evidence that the leading edge and actin might be involved in P. aeruginosa T3S translocation was initially obtained in studies of HT-29 epithelial cells, where Rac1, Cdc42, and actin polymerization at the leading edge were found to be required for P. aeruginosa T3S translocation (5). A potential role of host actin-plasma membrane association at the leading edge in T3S translocation was recognized in studies of both HT-29 and HL-60 cells, where cellular adherence to matrix (which stabilizes actin-plasma membrane associations) was found to correlate with T3S translocation efficiency (5).…”
Section: Discussionmentioning
confidence: 99%
“…T24 cells were seeded in chamber slides (Nalge Nunc International, Rochester, NY) 24 h prior to coculture for 1.5 h with P. aeruginosa expressing ExoS-WT or the pUCP plasmid control. Following coculture, T24 cells were washed twice in Dulbecco's phosphate-buffered saline (DPBS; HyClone), fixed in 3% paraformaldehyde in actin stabilization buffer (ASB) (5,26), permeabilized with 0.2% Triton X-100 in ASB, and blocked with 0.8% BSA, 0.1% fish gelatin, and 10 g/ml goat IgG. Cells were stained for F-actin by tetramethyl rhodamine isocyanate (TRITC)-phalloidin (Sigma-Aldrich), for P. aeruginosa by anti-P. aeruginosa lipopolysaccharide (LPS) (obtained from Joseph Lam, University of Guelph, Guelph, Ontario), and for trailing edge by anticaveolin-1 (N-20; Santa Cruz Biotechnology, Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations